Ladrões de gado: relações de trabalho e o direito de propriedade na fronteira oeste do Rio Grande do Sul (1888 - 1910) - Bahlis, Marcelo dos Santos (2019)
The present work tries to explain the rural conflicts, more precisely the thefts of animals, in two municipalities of the western border of Rio Grande do Sul, Alegrete and Uruguaiana, between 1888 and 1910: period of post-abolition, land concentration and transformation of the livestock economy and labor and property relations. The reading of the judicial sources demonstrated that the processes were opened criminalizing the rural workers of the Campaign for the most part. However, based on the attention given to the social logics and strategies used by the subjects involved in the conflicts, it was possible to perceive that only the explanation of the exclusion and land concentration does not account for all the existing conflicts, although some of the crimes are involved in situations of subsistence. Conflicts were seen as disputes in the field of law, negotiated in the strategies of reproduction of life. The evidence helps to affirm that many crimes were related to breaches in property relations, which underwent changes and still had agrarian customs involved. There were also found thieves full time, who had the theft of livestock and the sale of their by-products, a livelihood.